2000
DOI: 10.1128/aem.66.9.3987-3997.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Characterization of Bradyrhizobium Strains Nodulating Small Senegalese Legumes by 16S-23S rRNA Intergenic Gene Spacers and Amplified Fragment Length Polymorphism Fingerprint Analyses

Abstract: We examined the genotypic diversity of 64 Bradyrhizobium strains isolated from nodules from 27 native leguminous plant species in Senegal (West Africa) belonging to the genera Abrus, Alysicarpus, Bryaspis, Chamaecrista, Cassia, Crotalaria, Desmodium, Eriosema, Indigofera, Moghania, Rhynchosia, Sesbania, Tephrosia, and Zornia, which play an ecological role and have agronomic potential in arid regions. The strains were characterized by intergenic spacer (between 16S and 23S rRNA genes) PCR and restriction fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 45 publications
1
41
0
5
Order By: Relevance
“…S2). As a comparison, when bradyrhizobia nodulating Senegalese legumes were analysed by PCR-RFLP of the IGS with eight enzymes, the strains were clustered at a final level of similarity of 36 % (Doignon-Bourcier et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S2). As a comparison, when bradyrhizobia nodulating Senegalese legumes were analysed by PCR-RFLP of the IGS with eight enzymes, the strains were clustered at a final level of similarity of 36 % (Doignon-Bourcier et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The fragments produced with the primers were larger than those obtained by Willems et al (2001) and Doignon-Bourcier et al (2000), but we have used different primers. Cluster analysis of the RFLP products of the IGS resulted in two main great groups and isolated strains that were joined at a final level of similarity of 26?7 % (Table 1; Supplementary Fig.…”
Section: Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that individual groups of rhizobia were present at one site and rhizobia belonging to cluster 2 or 4 were present at all the sites. In case of Bradyrhizobium infecting tree legume, bradyrhizobial strains were clustered into 16 groups with six predominant groups [34]. Further symbiotic characterization of these rhizobia showed that mungbean rhizobia differed in number of nodules formed, nodule fresh weight, root dry weight, shoot dry weight and total N uptake by plant.…”
Section: Discussionmentioning
confidence: 99%
“…It plays also a big role in a taxonomy of microorganisms including classification and typing of nodule bacteria (Doignon-Bourcier et al, 2000;Duim et al, 2004;Gibson et al, 1998;Gürtler and Mayall, 2001;Savelkoul et al, 1999;Terefework et al, 2001).…”
Section: Introductionmentioning
confidence: 99%